1996
DOI: 10.1146/annurev.ecolsys.27.1.305
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory and Plant Defenses in Tropical Forests

Abstract: In this review, we discuss the ecological and evolutionary consequences of plantherbivore interactions in tropical forests. We note first that herbivory rates are higher in tropical forests than in temperate ones and that, in contrast to leaves in temperate forests, most of the damage to tropical leaves occurs when they are young and expanding. Leaves in dry tropical forests also suffer higher rates of damage than in wet forests, and damage is greater in the understory than in the canopy. Insect herbivores, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

77
1,811
30
80

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,730 publications
(2,051 citation statements)
references
References 158 publications
77
1,811
30
80
Order By: Relevance
“…While the median leaf nitrogen content for angiosperms usually ranges between approximately 1% and 5% (Mattson 1980;Lorenzo et al 2010), that of the same nutrient in A. blanchetiana leaves is considerably lower, varying from 0.4% to 0.6%. Some studies have shown that nitrogen concentration is significantly higher in younger leaves, rendering them more palatable than adult ones (Coley & Barone 1996;Nichols-Orians & Schultz 1990). Our results show the opposite in that the attacked distal portions of mature and old leaves of A. blanchetiana presented higher nitrogen content than the soft younger leaves.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…While the median leaf nitrogen content for angiosperms usually ranges between approximately 1% and 5% (Mattson 1980;Lorenzo et al 2010), that of the same nutrient in A. blanchetiana leaves is considerably lower, varying from 0.4% to 0.6%. Some studies have shown that nitrogen concentration is significantly higher in younger leaves, rendering them more palatable than adult ones (Coley & Barone 1996;Nichols-Orians & Schultz 1990). Our results show the opposite in that the attacked distal portions of mature and old leaves of A. blanchetiana presented higher nitrogen content than the soft younger leaves.…”
Section: Discussioncontrasting
confidence: 71%
“…Intraspecific preferences of herbivores are commonly related to within-plant heterogeneity of mechanical, morphological, chemical and nutritional properties (Coley 1983;Coley & Aide 1991). Also, biotic (e.g., previous damage by herbivores) and abiotic (sun and shade leaves) effects, in addition to leaf rolling and tissue development stage or age (e.g., younger versus older leaves), can affect foraging behaviour (Coley et al 1985.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa diferença de espessura é comumente considerada uma prevenção contra a transpiração (Larcher 2000), uma vez que todas as folhas estudadas encontram-se expostas à radiação solar plena. Além disso, a cutícula espessa pode funcionar como um repelente de água, auxiliando na secagem mais rápida da folha (Smith & McClean 1989) e como defesa contra a herbivoria, pois a cutícula incrementa a espessura da folha, contribuindo com a sua textura coriácea (Coley & Barone 1996).…”
Section: Resultsunclassified
“…The concentration of tannins in plant tissue may be determined by many factors, such as environmental conditions (i.e., water and nutrient availability; Herms & Mattson 1992;Shure et ai. 1998) and parameters related to the plant, mainly plant phenology (Feeny 1970;Espírito-Santo & Fernandes 1998), sex (Jing & Coley 1990;Herms & Mattson 1992), and age (Coley & Barone 1996).…”
Section: Introductionmentioning
confidence: 99%